Acute effects of intermittent fasting with aerobic exercise on weight loss among government sector workers with obesity - Norhishamuddin, Muhammad Amar Muzhaffran; Abu Kasim, Nurul Ain (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study evaluates the impact of combining intermittent fasting (16:8) with aerobic exercise on weight loss and BMI among obese government workers participating in the KBS “The Biggest Loser” program. Over a four-week intervention, twelve participants were divided to compare fasting alone against a combination of fasting and aerobic exercise performed three times weekly. By addressing the specific needs of sedentary occupational groups, the research aims to determine whether adding structured physical activity to dietary timing provides superior acute benefits for weight management and public health outcomes.